MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR SISWA PADA MATERI PEMUAIAN ZAT DI SMA - Imaniar, Eri Noorlita; Tandililing, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aimed of this research was to determine the implementation of Problem Based Learning model based on student learning outcomes in expansion material substance in class X  SMA Negeri 1 Noyan. This research used quasi experiment research was with  one group pretest-posttest design. Sampling was done by intact group sampling technique. The number of samples is 23 student consisting of class XA. The instrument used was an essay test. From the data analysis obtained an average score of student learning outcomes before being given treatment amounted to 18.6 while the average score of student learning outcomes after being given treatment amounted 32. The research showed that from the paired sample of T-test with a significant level of 5%  showed that Ha is accepted. From the calculator effect size obtained by 1.62 with criteria classified as high meaning concluded that the problem based learning model can improve student learning outcomes. Keywords:       Learning Outcomes, PBM Model, Substance Expansion